2014
DOI: 10.3136/fstr.20.1207
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Induced Egg White Isolate Gels with Various Microstructure

Abstract: Commercially available egg white isolates (EWI) or concentrates can not be used for ions-induced gelationbecause of high mineral content. In the present research new egg white isolate with reduced minerals content was applied for production of calcium induced gel. At 5.5% critical protein concentration no gel was obtained at the preheating process at 80℃ for 30 min. Increased calcium ions concentration formed more elastic gels with higher hardness, adhesiveness and chewiness. There was a linear correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…There is an optimal concentration of the ions, at which there is the highest value of viscosity and hardness. The increased calcium concentration creates gels with higher hardness and viscosity [19]. Similar tendencies observed for calcium ions were observed for other ions.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…There is an optimal concentration of the ions, at which there is the highest value of viscosity and hardness. The increased calcium concentration creates gels with higher hardness and viscosity [19]. Similar tendencies observed for calcium ions were observed for other ions.…”
Section: Resultssupporting
confidence: 70%
“…There is a linear correlation between the quadratic mean of the surface roughness (R q ) and the maximum roughness height (R t ) (R 2 = 0.98) (chart inside). Similar correlation was observed for the non-aerated egg white gels [19]. Chen et al [31] observed that whey protein gel obtained without the sodium ions addition had a very smooth surface, with R q and R a (arithmetic average of the collected roughness points) of 0.20 and 0.18 μm, respectively.…”
Section: Surface Roughnesssupporting
confidence: 69%
See 1 more Smart Citation
“…Egg-white gel has a very homogenous microstructure with very small particles (Figure 8c'). This phenomenon can be attributed to the fact that the egg-white protein isolate used in the research was an experimental preparation obtained by Kewpie Egg Corporation, which contained a very small concentration of ions [24,25]. Heat-induced gelation in the 0.2 NaCl solution resulted in a fine-stranded gel being obtained (Figure 8c') [26].…”
Section: Microstructurementioning
confidence: 99%